Al-Qur'an's View of The Process of Creation of Living Creatures and Its Implications for The Theory of Evolution - Hasibuan, Hotmaida (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The research was conducted to explore the relationship between the concept of creation contained in the Qur'an and its relation to modern biological theories, with a special focus on integrating scientific interpretation in understanding the process of creating living things. This study uses a literature review and a thematic exegesis approach, this study examines Qur'anic verses related to the process of creation of humans and other living things and compares them with contemporary biological theories. These findings reveal the harmony between the teachings of the Qur'an and scientific concepts, where the two can complement each other in providing a clearer understanding of the process of the creation of living things. This research also emphasizes the importance of integrating religion and science which can strengthen the relevance of the Qur'an in the context of modern scientific advancement. These findings contribute to the development of a better integrative education model and become a constructive dialogue between religion and science